Use of Complementary and Alternative Medicine in Children with Asthma. Issue 4 (2010) - Torres-Llenza, Vanessa; Bhogal, Sanjit; Davis, Michael; Ducharme, Francine M
Abstract : BACKGROUND: Because of the potential risk of interaction with, and underuse of, conventional medications, it is important to document the prevalence of the use of complementary and alternative medicines (CAMs) in asthmatic children. OBJECTIVE: To ascertain the prevalence and type of CAMs, and to identify factors associated with their use. METHODS: A cross-sectional survey of children who presented to the Asthma Centre of The Montreal Children's Hospital (Montreal, Quebec) between 1999 and 2007 was conducted. At the initial consultation, parents completed a questionnaire inquiring, in part, about CAM use. Computerized health records provided information regarding patient characteristics and their condition. RESULTS: The median age of the 2027 children surveyed was 6.1 years (interquartile range 3.3 to 10.5 years); 58% were male and 59% of children had persistent asthma. The prevalence of CAM use was 13% (95% CI 12% to 15%). Supplemental vitamins (24%), homeopathy (18%) and acupuncture (11%) were the most commonly reported CAMs. Multivariable logistic regression analysis confirmed the association of CAM use with age younger than six years (OR 1.86; 95% CI 1.20 to 2.96), Asian ethnicity (OR 1.89; 95% CI 1.01 to 3.52), episodic asthma (OR 1.88; 95% CI 1.08 to 3.28) and poor asthma control (OR 1.98; 95% CI 1.80 to 3.31). CONCLUSION: The prevalence of reported CAM use among Quebec children with asthma remained modest (13%), with vitamins, homeopathy and acupuncture being the most popular modalities. CAM use was associated with preschool age, Asian ethnicity, episodic asthma and poor asthma control.